Meningiomas in Premenopausal Women: Role of the Hormone Related Conditions - Maiuri, Francesco; Mariniello, Giuseppe; Somma, Teresa; Guadagno, Elia; Corvino, Sergio; Pagano, Serena; Orlando, Valentina; Del Basso De Caro, Marialaura (Frontiers in Oncology, 2020)
Background: Several epidemiological and pathological findings suggest that the female sex hormones may influence the development of meningiomas. However, the role of pregnancy, oral contraceptives and fertilization therapies is still controversial. Methods: From the surgical series of 354 patients with meningiomas operated on between 2006 and 2019, the group of 72 premenopausal women was separately considered. The tumor location, WHO grade, Ki67-labelling index (LI), progesterone receptor (PR) expression and histological types were studied in premenopausal women with and without hormone-related conditions. Results: In this premenopausal group, 24 patients had hormone-related conditions, including use of oral contraceptives in 16, intrauterine fertilization in one, pregnancy in 3 and tumors of the female reproductive system in 4. The group of patients with hormone-related conditions, as compared to that with no hormone related conditions, showed slightly lower median age (38 versus 43 years) and no significant difference of meningioma location WHO grade, Ki 67-Li, PR expression and histological type. The clinical onset during pregnancy in 3 patients and tumor growth during contraceptive progesterone therapy in two others were evidenced. Conclusion: The biological behaviour of meningiomas and their pathological findings, including PR expression, are not correlated with the different hormone related conditions in premenopausal female patients. Contraceptives and fertilization therapies, mainly with progesterone, should be avoided in patients with meningiomas